A method for preparing La-deficient LaFeO3 and its use in degrading estrogen

By introducing La defects into LaFeO3 perovskites, the La defective LaFeO3/PMS system is formed, which solves the problem of low estrogen degradation in the prior art, and achieves efficient degradation of various pollutants and high stability and reusability of materials.

CN119771423APending Publication Date: 2025-04-08AGRO ENVIRONMENTAL PROTECTION INST OF MIN OF AGRI
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411964889.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

The prior art has problems of low efficiency and complex material design in degrading estrogen, especially in the catalytic oxidation process of perovskite materials, which needs to be further improved.

Method used

By introducing La defects into LaFeO3 perovskites, the particle size, pores and surface element state of the material are changed, the Fe redox capacity is improved, and the persulfate oxidant is activated to form a La defective LaFeO3/PMS system to improve the catalytic degradation performance.

Benefits of technology

It has achieved efficient degradation of various pollutants, especially under a variety of coexisting substances, a wide pH environment and multiple recycling conditions, showing excellent catalytic capacity, high stability and high reusability, providing new ideas for the efficient degradation of trace organic pollutants in aquaculture wastewater.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119771423A_ABST
    Figure CN119771423A_ABST
Patent Text Reader

Abstract

The present invention relates to a La-deficient LaFeO3 preparation method and its use in degrading estrogen, comprising the following steps: dissolving La(NO3)3·6H2O, Fe(NO3)3·9H2O and citric acid in deionized water to obtain a mixed solution, wherein the ratio of La / Fe is 0.5-0.9; drying the mixed solution after hydrothermal treatment at high temperature; grinding the obtained product, calcining in sections, and crushing to obtain a La-deficient LaFeO3 catalyst for activating a persulfate oxidant to degrade β-estradiol. The present invention can change the particle size, pores, and elemental state of the surface of the perovskite material by introducing La defects at the A position of the LaFeO3 perovskite, so that the La-deficient LaFeO3 / PMS system shows stronger degradation performance for trace organic pollutants such as β-E2 in aquaculture wastewater, providing a new idea for the technology in the efficient degradation of aquaculture wastewater, and having great potential for practical application.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of estrogen degradation, and in particular to a method for preparing La-deficient LaFeO3 and application thereof in degrading estrogen. Background Art

[0002] Estrogen is a cholesterol-based bioactive hormone, mainly produced by the adrenal cortex, testicles, ovaries and placenta of animals. It has attracted attention due to its negative impact on biological health and the environment. The four most common natural and synthetic steroid estrogens in the world include estrone (E1), α-estradiol (α-E2), β-estradiol (β-E2), ethinyl estradiol (EE2) and estriol (E3). Among them, the C17 position of E2 is substituted, showing stronger resistance to degradation compared with other estrogens. Estrogen in the environment comes from human and animal excrement, pharmaceuticals, dairy products, poultry and meat industries, among which animal manure is the main source, especially the manure and wastewater of concentrated livestock and poultry. The steroid estrogens in livestock and poultry wastewater are 100 times higher than those in urban sewage and 1000 times higher than the limit concentration for endocrine system disorders in wild animals. Excessive estrogen can simulate or interfere with the normal operation of endogenous estrogen in the body after entering the organism, causing disorders of the endocrine system, reproductive system and nervous system of the organism, and affecting the health of the organism. Currently, the EU has formulated relevant emission standards for β-E2, but China lacks relevant treatment technologies and standards. Therefore, it is very important to carry out research on β-E2 treatment technology in livestock and poultry wastewater.

[0003] The main treatment technologies for estrogen include adsorption, biological and advanced oxidation. The adsorption method can only transfer β-E2 from the liquid phase to the solid phase and cannot achieve the degradation of β-E2. The removal of β-E2 in the sludge of the biological method has become a new problem. The advanced oxidation method uses free radicals to react with persistent organic pollutants to mineralize them into CO2 and H2O. It has high chemical stability and low biodegradability. The core of this technology is to build an oxidant and catalyst combined treatment system. The persulfate (PMS) oxidation method is a method of using persulfate as an oxidant to degrade β-E2. The sulfate free radical is highly praised for its strong oxidation ability (Eo = 2.5-3.1V), long life (30-40μs) and high selective oxidation. In recent years, perovskite has received widespread attention in the fields of solar energy, electrochemistry, sensors, catalytic oxidation, etc., and has been proven to be a catalyst with great potential. However, at present, perovskite degradation of estrogen is mainly through photocatalysis such as ultraviolet light. The material design and preparation are complex and the catalytic efficiency needs to be further improved, so it needs further improvement. Summary of the invention

[0004] The technical problem to be solved by the present invention is to overcome the deficiencies in the prior art and provide a method for preparing La-deficient LaFeO3 and its use in degrading estrogen.

[0005] The present invention is achieved through the following technical solutions:

[0006] A method for preparing La-deficient LaFeO3 comprises the following steps:

[0007] S1. Dissolve La(NO3)3·6H2O, Fe(NO3)3·9H2O and citric acid in deionized water to obtain a mixed solution, wherein the ratio of La / Fe is 0.5-0.9;

[0008] S2. The mixed solution is subjected to hydrothermal treatment at high temperature and then dried;

[0009] S3. The obtained product is ground, calcined in stages, and crushed to obtain a La-deficient LaFeO3 catalyst.

[0010] According to the above technical solution, preferably, in step S1, (La / Fe) and citric acid are dissolved in 50 mL of deionized water in a molar ratio of 1:2.

[0011] According to the above technical solution, preferably, step S2 comprises: subjecting the mixed solution to hydrothermal treatment in an oven at 180°C for 12 hours; washing the product with deionized water and ethanol after the reaction; and drying in an oven at 60°C for more than 10 hours after washing.

[0012] According to the above technical solution, preferably, in step S3, the obtained product is ground and then transferred to a quartz boat, which is placed in a tube furnace, and the heating rate is set to 5°C / min.

[0013] According to the above technical solution, preferably, in step S3, calcination is carried out at 400°C for 3 hours, the temperature is raised to 800°C for calcination for 3 hours, and a powdered sample is obtained after cooling, namely the La-deficient LaFeO3 catalyst.

[0014] The present application also discloses a use of La-deficient LaFeO3 in degrading estrogen. Based on the above-mentioned method for preparing La-deficient LaFeO3, the La-deficient LaFeO3 catalyst can activate a persulfate oxidant to degrade β-estradiol.

[0015] According to the above technical solution, preferably, the La-deficient LaFeO3 catalyst increases the catalytic active sites and can induce accelerated electron transfer, thereby increasing the charge transfer in the Fe(III)-Fe(II)-Fe(III) redox cycle, activating the persulfate to generate free radicals and non-free radicals, and degrading β-estradiol.

[0016] According to the above technical solution, preferably, the La-deficient LaFeO3 catalyst prepared by using La(NO3)3·6H2O and Fe(NO3)3·9H2O raw materials, wherein the La / Fe ratio is 0.7, is used to activate the persulfate oxidant to degrade β-estradiol.

[0017] According to the above technical solution, preferably, the La-deficient LaFeO3 catalyst can be - and NO3 - In a coexisting ion environment and at a pH of 5-7, it is used to activate the persulfate oxidant to degrade β-estradiol.

[0018] According to the above technical solution, preferably, the La-deficient LaFeO3 catalyst can be recycled within 6 times, and / or can be used to catalyze the degradation of TC, NOR, SDZ, EE2, BPA, ENR, CIP organic pollutants, and the removal rate reaches more than 85%.

[0019] The beneficial effects of the present invention are:

[0020] The present invention introduces La defects at the A position of LaFeO3 perovskite to change the particle size, pores, and elemental state of the surface of the perovskite material, improve the Fe redox ability, and significantly improve its ability to activate persulfate. Its unique defect structure promotes the LaFeO3 charge transfer efficiency and increases the charge transfer in the Fe(III)-Fe(II)-Fe(III) redox cycle. As a result, the La-deficient LaFeO3 / PMS system exhibits stronger degradation performance for a variety of pollutants, and also shows excellent catalytic ability, high stability, and high reusability under a variety of coexisting substances, a wide pH environment, and multiple recycling conditions, providing a new idea for the technology to efficiently degrade trace organic pollutants such as β-E2 in aquaculture wastewater, and has great potential for practical application. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 These are SEM / TEM images of LFO and 0.7LFO in the present invention, wherein (ab) are SEM images of LFO, (c) is TEM image of LFO, (de) is SEM image of 0.7LFO, and (f) is TEM image of 0.7LFO.

[0022] Figure 2 It is a schematic diagram of the physical properties of LFO and 0.7LFO in the present invention.

[0023] Figure 3These are the FT-IR, XPS and EPR spectra of LFO and 0.7LFO in the present invention, wherein: (a) FT-IR spectra of LFO and 0.5-0.9LFO, (b) XPS spectra of O1s, La 3d and Fe2p in LFO and 0.7LFO, (c) XPS spectra of O 1s, (d) XPS spectra of La 3d, (e) XPS spectra of Fe2p, and (f) EPR spectra of LFO and 0.7LFO.

[0024] Figure 4 is the ratio of La to Fe in LFO, 0.7LFO EDS, ICP and XPS of the present invention.

[0025] Figure 5 It is the pseudo-first-order kinetic fitting of the catalytic degradation process of the present invention, wherein (a) represents the pseudo-first-order kinetic fitting of the catalyst degradation process with different La / Fe ratios, and (b)-(f) represent the pseudo-first-order kinetic fitting of the degradation process with different persulfate concentrations, catalyst dosages, pH values, and coexisting substances.

[0026] Figure 6 1 is a diagram for evaluating the effect of different influencing factors on the catalyst in the present invention, including: (a) different catalysts, (b) different PMS concentrations, (c) different catalyst dosages, (d) different pH conditions, (e) Zeta potential diagram of 0.7LFO, and (f) coexisting substances.

[0027] Figure 7 The present invention discloses a catalyst for the reusability, stability and practical application of the catalyst, wherein: (a) the cycle performance of 0.7LFO / PMS in degradation of β-E2; (b) the iron leaching amount and TOC degradation rate of 0.7LFO cycle (target pollutant concentration = 2mg / L, catalyst dosage = 5mg, V = 50mL, PMS = 400mg / L, pH = 7, reaction time = 1h); (c) 0.7LFO / PMS degradation of different pollutants (pollutant concentration = 2mg / L, catalyst dosage = 5mg, V = 50mL, PMS = 400mg / L, reaction time = 1h); and (d) actual wastewater experiment (catalyst dosage = 5mg, V = 50mL, PMS = 400mg / L, pH = 7, reaction time = 2h).

[0028] Figure 8 The reaction mechanism of the degradation process of β-E2 in the 0.7LFO / PMS system of the present invention, wherein (a) quenching experiment, (b) TEMP- 1 ESR spectra of O2, (c) DMPO-·OH and ·SO4 -(d) ESR spectrum of 0.7LFO after catalysis, (e) XPS Fe 2p spectrum of 0.7LFO after catalysis, (f) XPS La 3d spectrum of 0.7LFO after catalysis, (g) XRD pattern of 0.7LFO after catalysis, (h) SEM image of 0.7LFO after catalysis.

[0029] Fig. 9 This is a diagram showing the mechanism of degradation of β-E2 by the 0.7LFO / PMS system of the present invention. DETAILED DESCRIPTION

[0030] In order to enable those skilled in the art to better understand the technical solution of the present invention, the present invention is further described in detail below in conjunction with the accompanying drawings and the best embodiment. Based on the embodiments in the invention, all other embodiments obtained by ordinary technicians in the field without creative work are within the scope of protection of the invention.

[0031] The ideal ABO3 perovskite structure contains equal amounts of cations in its A and B sites (i.e., the A / B cation molar ratio is 1:1). The perovskite structure itself is highly stable and can tolerate relatively more defects, such as cation defects and oxygen defects. Cation defects can induce defect dipoles, which then generate local electric fields to promote charge separation. The introduction of A-site cation defects in the lattice structure of perovskites can significantly change the physical and chemical properties of perovskites, and crystal defects can serve as active sites in heterogeneous catalytic processes. The special electronic configuration of Fe in LaFeO3 makes it very easy to gain and lose electrons, which can effectively activate PMS and has a smaller environmental burden and economic cost than Co and Ag. In addition, it has a stable structure with up to 30% La-site cation defects. LaFeO3 with A-site defects has been explored for application in the fields of electrocatalysis and gas catalysis. There is still a lack of direct evidence for the application of La-deficient LaFeO3 in the treatment of emerging organic pollutants such as estrogen. The charge transfer and free radical types of the catalytic oxidation process of La-deficient LaFeO3 perovskite in the persulfate system still need to be further clarified. The preparation method determines the parameters such as the perovskite morphology, grain size, specific surface area, and pore size. The hydrothermal method and the sol-gel method are simple to operate, the morphology and size are easy to control, and the catalytic performance is excellent. This application adopts the sol-gel method and the hydrothermal method to prepare LaFeO3 with different concentrations of La defects. The morphology and electronic structure of the cation-defective LaFeO3 are clarified through characterization and analysis. The performance and reaction parameters of LaFeO3 / persulfate oxidation degradation of estrogens such as β-E2 are explored and optimized. It is proved that the introduction of La defects to induce accelerated electron transfer and the formation of more active sites, and a variety of free radical and non-free radical oxidation pathways are the reasons for improving the catalytic efficiency, which provides new ideas for the efficient degradation of trace organic pollutants such as β-E2 in aquaculture wastewater by this technology.

[0032] Example 1: The present application discloses a method for preparing LaFeO3 perovskite by a citric acid sol-gel method, the specific steps of which include:

[0033] S1. Dissolve 0.02 mol La(NO3)3·6H2O, 0.02 mol Fe(NO3)3·9H2O and 0.1 mol citric acid in 300 mL deionized water so that the molar ratio of (La+Fe) to citric acid is 1:2.5;

[0034] S2. The mixed solution was transferred to a constant temperature water bath at 80°C to evaporate the water to obtain a wet gel, and then placed in an oven at 120°C to dry for 24 hours to obtain a dry gel;

[0035] S3. The dry gel was crushed and ground and transferred to a quartz boat, which was placed in a tube furnace and the heating rate was set to 5°C / min. The mixture was calcined at 400°C for 3 h, then heated to 800°C for 3 h, and cooled to room temperature to obtain a powdered sample named LFO.

[0036] Example 2: The present application discloses a method for preparing La-deficient LaFeO3, comprising the following steps:

[0037] S1. Dissolve La(NO3)3·6H2O, Fe(NO3)3·9H2O and citric acid in deionized water to obtain a mixed solution, wherein the ratio of La / Fe is 0.5-0.9. Specifically, in this example, (La / Fe) and citric acid are preferably dissolved in 50 mL of deionized water in a molar ratio of 1:2, wherein the ratio of La / Fe is selected from 0.9, 0.8, 0.7, 0.6, and 0.5;

[0038] S2. The mixed solution was subjected to hydrothermal treatment at high temperature and then dried. Specifically, the mixed solution was transferred to a 100 mL polytetrafluoroethylene-lined reactor and subjected to hydrothermal treatment in an oven at 180 ° C for 12 h. After the reaction, the product was washed twice with deionized water and ethanol, and then dried in an oven at 60 ° C for more than 10 h;

[0039] S3. After grinding the obtained product, calcining it in stages, and crushing it to obtain La-deficient LaFeO3 catalyst. Specifically, after grinding the obtained product, transfer it to a quartz boat, place it in a tubular furnace, set the heating rate to 5°C / min, calcine at 400°C for 3h, heat to 800°C and calcine for 3h, and cool to room temperature to obtain powdered samples, i.e., the La-deficient LaFeO3 catalysts, named 0.5LFO, 0.6LFO, 0.7LFO, 0.8LFO, and 0.9LFO, respectively.

[0040] Scanning electron microscope (SEM) and TEM are used to analyze the material morphology, surface element distribution, and lattice spacing. Figure 1 As shown. Figure 1 As shown in (a)-(b), LFO has a block-like morphology composed of approximately 100 nm ellipsoidal nanostructures. Figure 1 As shown in (d)-(e), 0.7LFO is a spherical structure with 20-30nm ellipsoidal nanostructures and a large number of pores distributed on the surface, showing a smaller particle size and more pores, which is conducive to providing abundant adsorption and catalytic sites for the reaction. TEM further evaluated the structural characteristics of the material. The grain size is consistent with the SEM observation results. All materials show obvious lattice fringes, such as Figure 1 As shown in (c), the lattice spacings of the (200) and (110) planes of LFO are 0.277 and 0.391 nm, respectively, which are consistent with the PDF card parameters. Figure 1 (f) shows that the lattice spacings of the two crystal planes of 0.7LFO are 0.276 and 0.390 nm, respectively, indicating that the lattice shrinks slightly. In addition, an obvious disordered structure is observed in the 0.7LFO sample ( Figure 1 (f) Circle), the disordered structure belongs to La defects.

[0041] also, Figure 2 As for the physical properties of the catalyst, the specific surface area, average pore size and pore volume of 0.7LFO are 3.90, 5.43 and 1.39 times that of LFO, respectively. La defects may provide more active sites for the catalytic reaction, which is consistent with the SEM results.

[0042] like Figure 3 As shown in (b), the XPS spectrum shows characteristic peaks corresponding to O1s, La 3d, and Fe 2p. The peaks 532.19, 531.00, and 528.84 eV in the O1s spectrum correspond to the adsorbed molecular water, adsorbed oxygen (O ads ) and lattice oxygen (O lat ). Usually O ads / O lat The oxygen defect concentration of 0.7LFO decreased by 35.32% compared with that of LFO. 5 / 2 and La 3d 3 / 2 The peaks correspond to 834.07 and 850.80 eV, respectively. The spin-orbit splitting energy of La in both catalysts is 16.62 eV, indicating that La ions mainly exist in the +3 form. All characteristic peaks of 0.7LFO are shifted to the direction of high binding energy, and its electron cloud density decreases with electron migration. The obvious reduction in the La 3d peak area of ​​the 0.7LFO sample is also consistent with La defects. The Fe 2p spectrum of LFO is Fe 3+ (710.28 and 723.98 eV) and Fe 2+The two sets of spin-orbit splitting peaks (2p 3 / 2 and 2p 1 / 2 ) and satellite peaks. After the La defect is introduced, the 718.98eV satellite peak moves toward the low binding energy direction and a new Fe 3+ The satellite peaks are attributed to the increase in electron cloud density and the occurrence of charge transfer. 3 / 2 ΔBE changes from 4.2 to 2.06, Fe 2p 1 / 2 The ΔBE of the characteristic peak changes from 3.7 to 2.6, indicating that the electron cloud density decreases and charge transfer occurs, that is, after the introduction of La defects, the lattice may maintain electrical neutrality through charge transfer or oxygen defects. In 0.7LFO, oxygen defects decrease, indicating that material charge compensation is dominant. The introduction of La defects leads to the Fe 3+ The proportion of materials has increased significantly (such as Figure 4 As shown in Figure 2, high-valent metals often exhibit better catalytic performance. XPS calculations and ICP-MS results show that the La / Fe ratio in 0.7LFO is 0.66 ( Figure 4 ), which is significantly lower than the ratio of LFO, which is consistent with the La defect. The La / Fe atomic content ratio is reduced, and the surface of the material with La defects will expose more iron and Fe-O bonds, which is beneficial to improve the catalytic efficiency.

[0043] Example 3: The present application also discloses a use of La-deficient LaFeO3 in degrading estrogen. Based on the above-mentioned method for preparing La-deficient LaFeO3, the La-deficient LaFeO3 catalyst can activate a persulfate oxidant to degrade β-estradiol. Specifically, the La-deficient LaFeO3 catalyst increases the catalytic active sites and can induce accelerated electron transfer, thereby increasing the charge transfer in the Fe(III)-Fe(II)-Fe(III) redox cycle, activating the persulfate to generate free radicals and non-free radicals, and degrading β-estradiol.

[0044] The catalytic experiments for evaluating the effect of the catalyst in this example were all carried out in a solution prepared with deionized water. Preferably, 5 mg of the catalyst was weighed and loaded into a 100 mL conical flask, 50 mL and 2 mg / L of β-E2 were added, and the pH value was adjusted to 7 using HCl and NaOH. The flask was placed in a shaking flask incubator at 25 ° C and 150 rpm for 30 min of adsorption reaction. After the adsorption-desorption equilibrium was established, 400 mg / L PMS was added to start the catalytic reaction. During the reaction, the sampling interval was 10 min and the reaction time was 1 h. The supernatant was filtered through a 0.22 μm membrane filter, and the concentration of β-E2 was determined by high performance liquid chromatography (HPLC-Agilent1260, USA) and a C18 chromatographic column (4.6 mm×250 mm). To ensure the accuracy of the data, the experiments were repeated 3 times. The degradation kinetics of the pollutant were evaluated according to the degradation rate (η) using the following formula, and the apparent rate constant (k) was calculated using the proposed first-order kinetic equation.

[0045]

[0046] Where, t is the reaction time, min; C0 and C t are the initial concentration and real-time concentration of the solution, mg / L respectively.

[0047] In addition, the persulfate concentration (0, 50, 100, 200, 400, 800 mg / L), catalyst dosage (0, 1, 2, 5, 10, 20 mg), pH value (3, 5, 7, 9, 11), coexisting substances (Cl - 、NO3 - 、HCO3 - 、CO3 2- , HA), pollutant types (TC, NOR, SDZ, EE2, BPA, ENR, CIP) and material recycling experiments were performed to evaluate catalyst performance.

[0048] (1) Persulfate concentration:

[0049] All catalytic experiments were conducted in solution. Weigh 5 mg of catalyst and put them into 100 mL conical flasks, add 50 mL and 2 mg / L β-E2, and adjust the pH to 7 with HCl and NaOH. Place the flask in a shaking incubator at 25 ° C and 150 rpm. After 30 min of adsorption reaction to establish adsorption-desorption equilibrium, 0, 50, 100, 200, 400, and 800 mg / L PMS were added to start the catalytic reaction. During the reaction, the sampling interval was 10 min and the reaction time was 1 h. The supernatant was filtered through a 0.22 μm membrane filter and the concentration of β-E2 was determined by high performance liquid chromatography (HPLC-Agilent 1260, USA) and C18 column (4.6 mm × 250 mm). The experiment was repeated three times.

[0050] (2) Catalyst dosage:

[0051] All catalytic experiments were conducted in solution. 0, 1, 2, 5, 10, and 20 mg of catalyst were weighed and loaded into 100 mL conical flasks, 50 mL and 2 mg / L β-E2 were added, and the pH value was adjusted to 7 using HCl and NaOH. The flask was placed in a shaking flask incubator at 25 ° C and 150 rpm. After 30 min of adsorption reaction to establish adsorption-desorption equilibrium, 400 mg / L PMS was added to start the catalytic reaction. During the reaction, the sampling interval was 10 min and the reaction time was 1 h. The supernatant was filtered through a 0.22 μm membrane filter and the concentration of β-E2 was determined using high performance liquid chromatography (HPLC-Agilent 1260, USA) and a C18 column (4.6 mm × 250 mm). The experiment was repeated three times.

[0052] (3) pH environment:

[0053] All catalytic experiments were conducted in solution. Weigh 5 mg of catalyst and put them into 100 mL conical flasks, add 50 mL and 2 mg / L β-E2, and adjust the pH to 3, 5, 7, 9, and 11 respectively with HCl and NaOH. Place the flask in a shaking incubator at 25 ° C and 150 rpm. After 30 min of adsorption reaction to establish adsorption-desorption equilibrium, 400 mg / L PMS was added to start the catalytic reaction. During the reaction, the sampling interval was 10 min and the reaction time was 1 h. The supernatant was filtered through a 0.22 μm membrane filter, and the concentration of β-E2 was determined by high performance liquid chromatography (HPLC-Agilent 1260, USA) and C18 chromatographic column (4.6 mm × 250 mm). The experiment was repeated three times.

[0054] (4) Coexisting substances:

[0055] All catalytic experiments were conducted in solution. Weigh 5 mg of catalyst and put them into 100 mL conical flasks, add 50 mL, 2 mg / L β-E2, and then add 200 mg / L KCl, KHCO3, K2CO3, and KNO3. Place the flask in a shaking incubator at 25°C and 150 rpm. After 30 minutes of adsorption reaction to establish adsorption-desorption equilibrium, 400 mg / L PMS was added to start the catalytic reaction. During the reaction, the sampling interval was 10 minutes and the reaction time was 1 hour. The supernatant was filtered through a 0.22 μm membrane filter and the concentration of β-E2 was determined by high performance liquid chromatography (HPLC-Agilent 1260, USA) and a C18 column (4.6 mm×250 mm). The experiment was repeated three times.

[0056] All catalytic experiments were carried out in solution. 5 mg of catalyst was weighed and placed in 100 mL conical flasks, and 50 mL, 2 mg / L β-E2 and 20 mg / L HA were added. The flasks were placed in a shaking incubator at 25 ° C and 150 rpm. After 30 minutes of adsorption reaction to establish adsorption-desorption equilibrium, 400 mg / L PMS was added to start the catalytic reaction. During the reaction, the sampling interval was 10 minutes and the reaction time was 1 hour. The supernatant was filtered through a 0.22 μm membrane filter and the concentration of β-E2 was determined using high performance liquid chromatography (HPLC-Agilent1260, USA) and a C18 column (4.6 mm×250 mm). The experiment was repeated three times.

[0057] (4) Types of pollutants:

[0058] All catalytic experiments were conducted in solution. 5 mg of catalyst was weighed and placed in 100 mL conical flasks, and 50 mL, 2 mg / L sulfadiazine, norfloxacin, 17α-EE2, bisphenol A, ciprofloxacin, enrofloxacin, and tetraflavin were added. The flasks were placed in a shaking flask incubator at 25 ° C and 150 rpm. After 30 min of adsorption reaction to establish adsorption-desorption equilibrium, 400 mg / LPMS was added to start the catalytic reaction. During the reaction, the sampling interval was 10 min and the reaction time was 1 h. The supernatant was filtered through a 0.22 μm membrane filter and the concentration of β-E2 was determined by high performance liquid chromatography (HPLC-Agilent 1260, USA) and C18 chromatographic column (4.6 mm × 250 mm). The experiment was repeated three times.

[0059] (5) Reuse:

[0060] After each catalytic experiment, the used catalyst was collected, washed with ethanol and pure water, filtered, and dried in an oven at 60°C for later use.

[0061] The La-deficient LaFeO3 catalyst prepared by using La(NO3)3·6H2O and Fe(NO3)3·9H2O as raw materials and the La / Fe ratio being 0.7 is used to activate the persulfate oxidant to degrade β-estradiol.

[0062] The performance and parameters of XLFO / PMS system for catalytic degradation of β-E2 were evaluated and optimized by adjusting the reaction conditions. Before adding PMS, all experiments were performed by adsorbing the pollutants for 30 minutes to establish adsorption-desorption equilibrium. The pseudo-first-order kinetics of the catalytic degradation process were fitted as shown in the figure. Figure 5 The removal rates of β-E2 by the seven catalysts were all less than 15%, and 0.7LFO showed the most significant β-E2 catalytic degradation performance, with a removal rate of 100% in 60 minutes (k = 0.07928min -1 ), the removal rates of LFO materials at other A-site vacancies are between 70% and 84.66%, while the removal rates of LFO and Fe2O3 are only 15.41% to 20.77%, and the pseudo-first-order kinetic constants of the 0.7LFO / PMS system are 22.03 and 63.63 times those of LFO and Fe2O3 ( Figure 5 (a)). Therefore, in all subsequent reaction condition optimization experiments, 0.7LFO was selected as the optimal defect-rich material.

[0063] Effect of PMS dosage on β-E2 removal Figure 6 As shown in (b), when the PMS concentration is 0, the β-E2 removal rate remains stable after 30 minutes of reaction, indicating that the catalyst has reached adsorption equilibrium. When the PMS concentration increases from 50 mg / L to 400 mg / L, the catalytic efficiency increases from 27.23% to 100%, which is attributed to the increase in the concentration of PSM to provide more free radicals. When the concentration increases to 800 mg / L, the catalytic rate decreases slightly, which is attributed to the self-scavenging phenomenon of free radicals caused by excessive PSM.

[0064] The effect of catalyst dosage on β-E2 removal is shown in Figure 6 (c) When the catalyst dosage is 0, it is equivalent to the pure PMS oxidation process. The β-E2 removal rate remains stable after 30 minutes of reaction, indicating that it is difficult for a simple oxidant to continuously degrade β-E2. When the catalyst dosage increases from 1 mg to 5 mg, the catalytic efficiency increases from 46.01% to 100%. The increase in catalyst dosage can provide more reaction sites. When the catalyst dosage reaches 20 mg, the k value increases from 0.08000min to 100%. -1 Down to 0.01973min -1 ( Figure 5 (c)), decreased by 4.05 times, which is related to the aggregation of excess catalyst in the solution.

[0065] The effect of solution pH on the catalytic degradation of β-E2 is shown in Figure 6 (d) The 0.7LFO / PMS system has a high removal rate of β-E2 in a wide pH range, and the catalytic efficiency is highest at pH 5-7, close to 100%. a1 <0, pK a2 =9.4, when pH <9.4, PMS is mainly in the form of HSO5 - It exists in the form of SO5 when pH>9.4 2- 0.7LFO zero charge point (pH PZC ) is 5.86( Figure 3 (e)), when the solution pH is less than 5.86, the surface charge of 0.7LFO is positive, that is, the positive charge on the surface of 0.7LFO is equal to HSO5 - The electrostatic attraction between them helps HSO5 - Adsorbed on the catalyst and activated to degrade pollutants. When the solution pH>pH PZC When 0.7LFO surface charge is negative, with HSO5 - and SO5 2- Electrostatic repulsion occurs, causing 0.7LFO to react with HSO5 - and SO5 2- The adsorption capacity decreases with the increase of pH, and under high pH conditions, the iron ions on the catalyst surface form hydroxide precipitation and cover the active sites, inhibiting the activation of PMS. Therefore, in this example, it is preferred but not limited to use La-deficient LaFeO3 catalyst in a pH 5-7 environment to activate the persulfate oxidant to degrade β-estradiol.

[0066] The effects of inorganic ions and humic acid (HA) on the catalytic degradation of β-E2 by 0.7LFO / PMS system are shown in Figure 6 (f), SO4 2- 、HCO3 - 、CO3 2- and HA have a significant inhibitory effect on the catalytic reaction, SO4 2- Will reduce SO4 - / SO4 2- The redox potential of HCO3 - Will react with ·OH and ·SO4 - The reaction generates free radicals with lower oxidizing power, resulting in ·OH and ·SO4 - is consumed, while HCO3 - and 1 O2 reacts to affect non-radical degradation pathways. CO3 2- Hydrolysis produces HCO3 - With ·OH, ·SO4 -The reaction inhibited PMS. - and NO3 - The reaction kinetic constants k under the coexistence conditions were 0.06869 and 0.06491 min, respectively. -1 , because of the low-activity free radicals produced, the inhibitory effect on the degradation process is not obvious. HA can directly compete with PSM and β-E2 for adsorption on the active sites on the catalyst surface, resulting in a decrease in the reaction rate. Therefore, the La-deficient LaFeO3 catalyst is preferably but not limited to being able to activate the persulfate oxidant to degrade β-estradiol in a variety of coexisting substances.

[0067]

[0068]

[0069] Analysis of catalytic performance of 0.7LFO material recycling process Figure 7 (a) After 6 cycles of 0.7LFO, the removal rate of β-E2 dropped from 100% to 74.31%, showing good reusability overall. The TOC mineralization degree during the 6 cycles is shown in Figure 2. Figure 7 (b), with the increase of the number of cycles, the TOC mineralization rate decreased, indicating that there are still intermediate organic products. At the same time, with the increase of the number of cycles, the amount of iron ion leaching showed a decreasing trend. After 6 cycles, the iron ion leaching rate was 0.191%, which was much lower than the iron leaching rate of 1.6% of iron-doped biochar, confirming the stability of 0.7LFO.

[0070] Degradation effects of various trace organic pollutants such as Figure 7 (c) Within 60 min, the removal rates of TC, NOR, SDZ, EE2, BPA, ENR, and CIP by the 0.7LFO / PMS system reached more than 85%, and the removal rates of NOR, ENR, and CIP were close to 100%, which was higher than the degradation effect of the LFO / PMS system, indicating that the 0.7LFO / PMS system can be widely used in the efficient degradation of various organic pollutants.

[0071] Therefore, in this example, it is preferred but not limited to that the La-deficient LaFeO3 catalyst can be recycled within 6 times, and can be used to catalyze the degradation of TC, NOR, SDZ, EE2, BPA, ENR, and CIP organic pollutants, and the removal rate reaches more than 85%.

[0072] At the same time, the present application has also been experimentally verified in actual wastewater, using wastewater from four dairy farms around Yunnan Province, China, and all wastewater has not been treated in any way. The initial pH of the aquaculture wastewater samples were 5.95±0.02, 6.89±0.02, 7.73±0.02 and 7.56±0.02, respectively. The initial concentrations of β-E2 were 1.63±0.10, 5.21±0.11, 6.58±0.07 and 6.17±0.09 mg / L, respectively. 5 mg of catalyst was weighed and loaded into a 50 mL conical flask, 50 mL of filtered wastewater sample was added, and the flask was placed in a shaking incubator at 25°C and 150 rpm. After a 30-minute adsorption reaction to establish the adsorption-desorption equilibrium, PMS was added to start the catalytic reaction, and the β-E2 concentration was measured after 2 hours of reaction. The actual degradation effect of β-E2 in dairy farming wastewater by the 0.7LFO / PMS system is shown in Figure 7 (d) After 120 min of catalytic reaction, the β-E2 removal rates of the four dairy wastewaters with β-E2 concentrations ranging from 1.63 to 6.58 mg / L reached 82.16%-99.25%, indicating that the 0.7LFO / PMS system has great application potential in the removal of β-E2 from complex dairy wastewater.

[0073] In addition, it is generally believed that SO4 - 、·OH、 1 O2 is the main active species produced during the PMS activation process. In order to determine the contribution of the three active species to the degradation of β-E2 in the 0.7LFO / PMS system, a free radical quenching experiment was conducted in this case. Figure 8 (a), MeOH or TBA with concentrations of 0.5, 1, and 2 M and 20 mM L-histidine were added. MeOH and SO4 - The reactivity with OH is very high (K ·SO4 - =1.6-7.7×10 7 M -1 s -1 , K ·OH =1.2-2.8×10 9 M -1 s -1 ), so MeOH can be used to quench SO4 - and ·OH, TBA can only quench ·OH(K ·OH =3.8-7.6×10 8 M -1 s -1 ), L-histidine quenching 1 O2. Add 0.5M methanol and tert-butanol, k increases from 0.08022min -1 Down to 0.04298min-1 and 0.04190min -1 When 2M methanol and tert-butyl alcohol were added, k dropped to 0.00222 and 0.00418 min, respectively. -1 , indicating that in the 0.7LFO / PMS system, OH is more than SO4 - The contribution is more important. When 20mM L-histidine is added, k drops to 0.01943min -1 , indicating that in the 0.7LFO / PMS system 1 O2 contributes less.

[0074] The reaction system was analyzed by ESR using TEMP and DMPO as free radical spin trapping agents to verify the charge transfer mechanism and free radical trapping results (e.g. Figure 8 (b)-(c)), two characteristic signals were detected, namely DMPO-·SO4 - (peak intensity is 1:1:1:1:1:1), DMPO-·OH (peak intensity is 1:2:2:1). As the 0.7LFO / PMS catalytic reaction proceeds, the Fe(III) / Fe(II) cycle may be promoted by charge transfer, resulting in enhanced ESR signals. - and ·OH play a decisive role in the reaction system. Figure 8 As shown in (b), the appearance of the 1:1:1 triplet signal further confirms that 1 The generation of O2 and the intensity of the reaction increased as the reaction progressed, indicating that the 0.7LFO / PMS system degraded β-E2 by SO4 - 、·OH、 1 O2 works together, and free radical pathways and non-free radical pathways coexist.

[0075] In order to explore the active sites of the catalytic reaction, the XPS characterization results of 0.7LFO after catalysis are as follows Figure 8 (d)-(f), Fe2p 1 / 2 The characteristic peak moves toward the low binding energy direction and ΔBE changes from 2.6 to 1.85, indicating that the electron cloud density decreases and charge transfer occurs. 3+ The disappearance of satellite peaks also indicates that charge transfer occurs. The Fe 2p peak area decreases significantly after catalysis, indicating that Fe is the main catalytic active site. The La 3d spectrum characteristic peaks do not change substantially, indicating that La is not an active site. lat The concentration decreased, O ads As the concentration increases, O lat The migration activation is O ads, increasing the oxygen vacancy concentration and providing more active sites for the catalytic reaction. This may be due to the La defect feature favoring the O lat migration, emission and intercalation, thereby enhancing the redox ability of the B site. Figure 8 (g) and (h) are the SEM and XRD images of 0.7LFO after 6 cycles, respectively. There is no obvious change in SEM and XRD compared with before catalysis, indicating that the material has good stability.

[0076] In summary, the activation mechanism of 0.7LFO / PMS is proposed. PMS is activated by charge transfer in the Fe(III)-Fe(II)-Fe(III) redox cycle to generate free radicals and non-free radicals ( Fig. 9 ). The Fe(III) on the surface of 0.7LFO transfers HSO5 - Oxidized to SO5 - , multiple SO5 - Combine to form O2 and SO4 - , while Fe(III) is reduced to Fe(II) and produces ·OH groups. - Combined with new HSO5 - Interaction to form Fe(II)-(HO)OSO3 - Complex. HSO5 - Charge transfer occurs to form ·OH. The introduction of La defects accelerates electron transfer and leads to ·SO4 - and ·OH are generated in large quantities. Oxygen vacancies may also be involved in activating persulfate. 1 O2-dominated non-radical pathways also contribute to the degradation of β-E2, mainly by HSO5 - and SO5 - Reaction generated.

[0077]

[0078] The present invention can change the particle size, pores, and elemental state of the surface of the perovskite material and improve the Fe redox ability by introducing La defects at the A-site of the LaFeO3 perovskite. The LaFeO3 perovskite oxide with A-site cation defects has significantly improved persulfate activation ability. Its unique defect structure promotes the LaFeO3 charge transfer efficiency and increases the charge transfer in the Fe(III)-Fe(II)-Fe(III) redox cycle. Therefore, the A-site cation defect LaFeO3 / PMS system exhibits stronger degradation performance for a variety of pollutants. After 60 minutes of reaction, 0.7LFO / PMS can degrade the initial concentration of 2mg / Lβ-E2 by 100%. The reaction rate constant (0.07954min -1), which is 22.03 times that of the original LFO / PMS system. The 0.7LFO / PMS system still has a good degradation effect under a variety of coexisting ions and humic acid substances, a wide range of pH environmental conditions, and multiple cycles, showing good stability and reusability of the material. In addition, the removal rate of β-E2 in actual dairy farming wastewater by 0.7LFO / PMS is as high as 82.16%-99.25%, which has great potential for practical application.

[0079] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing La-deficient LaFeO3, characterized in that: The steps include: S1. Dissolve La(NO3)3·6H2O, Fe(NO3)3·9H2O and citric acid in deionized water to obtain a mixed solution, wherein the ratio of La / Fe is 0.5-0.9; S2. The mixed solution is subjected to hydrothermal treatment at high temperature and then dried; S3. The obtained product is ground, calcined in stages, and crushed to obtain a La-deficient LaFeO3 catalyst.

2. The method for preparing La-deficient LaFeO3 according to claim 1, characterized in that: In step S1, (La / Fe) and citric acid were dissolved in 50 mL of deionized water at a molar ratio of 1:

2.

3. The method for preparing La-deficient LaFeO3 according to claim 1, characterized in that: Step S2 includes: The mixed solution was subjected to hydrothermal treatment in an oven at 180° C. for 12 h; After the reaction, the product was washed with deionized water and ethanol; After washing, the mixture was dried in an oven at 60°C for more than 10 h to obtain a dry gel.

4. The method for preparing La-deficient LaFeO3 according to any one of claims 1 to 3, characterized in that: In step S3, the obtained product is ground and then transferred to a quartz boat, which is placed in a tube furnace and the heating rate is set to 5°C / min.

5. The method for preparing La-deficient LaFeO3 according to claim 4, characterized in that: In step S3, calcination is performed at 400° C. for 3 h, and then the temperature is raised to 800° C. for calcination for 3 h. After cooling, a powdered sample is obtained, namely the La-deficient LaFeO3 catalyst.

6. Use of La-deficient LaFeO3 in degrading estrogen, based on the preparation method of La-deficient LaFeO3 according to claim 5, characterized in that: The La-deficient LaFeO3 catalyst can activate the persulfate oxidant to degrade β-estradiol.

7. The use of La-deficient LaFeO3 in degrading estrogen according to claim 6, characterized in that: The La-deficient LaFeO3 catalyst increases catalytic active sites and can induce accelerated electron transfer, thereby increasing charge transfer in the Fe(III)-Fe(II)-Fe(III) redox cycle, activating the persulfate to generate free radicals and non-free radicals, and degrading β-estradiol.

8. The use of La-deficient LaFeO3 in degrading estrogen according to claim 7, characterized in that: The La-deficient LaFeO3 catalyst prepared by using La(NO3)3·6H2O and Fe(NO3)3·9H2O raw materials with a La / Fe ratio of 0.7 is used to activate a persulfate oxidant to degrade β-estradiol.

9. The use of La-deficient LaFeO3 in degrading estrogen according to claim 8, characterized in that: The La-deficient LaFeO3 catalyst can be used in Cl - and NO 3- In a coexisting ion environment and at a pH of 5-7, it is used to activate the persulfate oxidant to degrade β-estradiol.

10. The use of La-deficient LaFeO3 in degrading estrogen according to claim 7, characterized in that: The La-deficient LaFeO3 catalyst can be recycled within 6 times, and / or It can be used to catalytically degrade TC, NOR, SDZ, EE2, BPA, ENR, and CIP organic pollutants, with a removal rate of more than 85%.